Identidade e escrita: o ethos discursivo em textos acadêmicos em Inglês como Língua Adicional - Isis Rodrigues Pordeus (2021)
Entering higher education poses many challenges for students, especially with regards to the production of written genres in the academic field. In the case of internationally educated nurses, immigrants, seeking their qualification and professional insertion in the Canadian health system, academic failure can have dramatic consequences. This work is an investigation about the discursive strategies of positioning (stance) in the production of texts in the academic domain, of a group of 7 health professionals taking a bridging program - a Bachelor of Nursing - at York University in Toronto / CA. The challenges represented by the demands of the intense production of texts from academic genres in the English language in this program, a language that these professionals know as a second language or, as we prefer, an additional language, are incomparable to the previous experience in their training as nurses. Our work is an excerpt that seeks to understand their textual production, in comparison with the publications of experienced authors from the academic-professional community of Nursing. We seek, as theoretical and methodological supports for this endeavor, assumptions of Critical Applied Linguistics (MOITA LOPES, 2006; PENNYCOOK 2001, 2007; RAJAGOPALAN, 2003), of the current theories that connect Language, Writing and Identity (HYLAND, 2005; IVANIC, 1998; NORTON, 2013; SIGNORINI, 1998), Argumentation Theory (AMOSSY, 2016; 2020) and the resources of corpus Linguistics tools (CALLIES, 2015; DUTRA, ORFANÓ, ALMEIDA, 2019; GILQUIN, GRANGER, PAQUOT, 2007; GRANGER, 2015). The results suggest that the participants approach, in several points, the practices of the academic-professional community of Nursing, in their discoursal practices in academic writing, but the points of divergence point to ways for the formation of foreign students in the learning of these genres. Above all, the results reveal the delicate balance between impersonality and visibility of the discoursal ethos, both of the participants and of the experienced writers of this community.